Hyper-IgE Syndrome in an Infant. Issue 4 (July 2016) - Giberson, Mariah; Finlayson, Laura
Background: Hyper–immunoglobulin E syndrome (HIES) is a rare primary immunodeficiency disorder that affects multiple systems. One of the early findings is a papulopustular rash, which has a wide differential diagnosis. Method: The authors report the case of a male newborn diagnosed with HIES. He presented with papulopustular dermatitis on the scalp. The authors also present a review of current theory on the pathophysiology, clinical presentation, and management of HIES. Conclusion: Although HIES is a multisystem disorder, many of the manifestations of HIES may present after the neonatal period. The cutaneous manifestations of HIES are usually present shortly after birth, and the presentation of pustules in a newborn may be one of the reasons a dermatologist would be asked to assess a patient in the neonatal period.